2021
DOI: 10.21203/rs.3.rs-469163/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antifungal Activity of Bacterial Strains from Maize Silks against Fusarium Verticillioides

Abstract: Fusarium verticillioides is pathogenic to maize and mycotoxin-producer, causing yield losses, feed and food contamination, and risks to human and animal health. Endophytic (ISD04 and IPR45) and epiphytic (CT02 and IM14) bacteria from maize silks were tested in vitro and greenhouse against F. verticillioides and for hydrolytic enzyme production (cellulase, pectinase, protease, lipase, and chitinase). The strains were assigned as Achromobacter xylosoxidans (ISD04), Pseudomonas aeruginosa (IPR45), and Bacillus ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In another study, Diniz et al (2021), analyzing the in vitro antifungal activity of four endophytic (ISD04 and IPR45) and epiphytic (CT02 and IM14) bacterial strains from maize silks, found inhibition values from 58.5 to 100%. In addition, the four isolates changed the hyphae morphology and inhibited the conidial germination by up to 100% (strain IPR45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Diniz et al (2021), analyzing the in vitro antifungal activity of four endophytic (ISD04 and IPR45) and epiphytic (CT02 and IM14) bacterial strains from maize silks, found inhibition values from 58.5 to 100%. In addition, the four isolates changed the hyphae morphology and inhibited the conidial germination by up to 100% (strain IPR45).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Diniz et al (2021) tested four endophytic and epiphytic bacteria from maize silks in vitro experimental plots), Sidrolândia-MS (field maize), Goiânia-GO (Embrapa Rice and bean, experimental plots) and Sertaneja-PR (field maize) in the 2016 harvest were randomly collected.…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial microbes can interact with pathogens directly or indirectly by inducing host resistance [43][44][45]. A recent study reported culturing of bacteria from maize silks in Brazil and found promising candidates for biocontrol of Fusarium verticillioides stalk rot and stored grains [46,47]. This study sampled environmentally exposed silk tissue from cobs randomly collected from fields.…”
Section: Introductionmentioning
confidence: 99%
“…There are many kinds of active substances that can eradicate fungi, including antifungal proteins (Chlebek et al, 2020), polypeptides (Li et al, 2021), phenolic weight fungal cell wall hydrolases or oxidases. Secretion of antifungal proteins is one of the important mechanisms by which bacteria kill the infected fungi, and antifungal proteins also constitute the basis of biocontrol of fungal diseases and plant antifungal genetic engineering (Diniz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%